Industries' requirements and expectations of graduates: a revisit - Md. Yusof, Masdinah Alauyah (LSP International Journal, 2018)
Graduate employability has become more rigid nowadays whereby industries demand not only for graduates’ academic qualifications but also their ability to communicate in English. However, there is hardly any exit test instrument available in higher learning institutions that could gauge the graduates’ communicative competence before graduation. Thus, to address this matter, the Test of English for Communication Skills (UTM-TECS) was developed aims to provide potential employers with a more accurate measure of graduates’ readiness to function in the workplace. Given that the demand of English in the workplace is continuously changing through time, it is therefore important to ensure the assessment scale used to assess graduates’ oral competency takes into account the latest and up-dated requirements and expectations sought by industries. Hence, this study was conducted to investigate the current criteria that the industries adopt in recruiting new graduates. Besides that, the study also aims to compare the industries’ assessment criteria with the criteria used in the UTM-TECS scale. This study utilized interviews as the data collection method and eight Human Resource personnel from different firms in Johor Bahru and Kuala Lumpur were involved. The study reveals that academic degree is needed for screening purposes; i.e. to shortlist the potential employees. In addition to that, soft skills which comprise of communication skill especially the English language speaking skill, team work, attitude, professional image and critical thinking ability are amongst the criteria used to select graduates for employment. It was discovered that the criteria listed by the respondents were almost similar to the criteria found in the scale except for one criterion; attitude which is not present in the UTM-TECS assessment scale. The respondents also viewed professional image as the highest of importance as compared to the UTM-TECS assessment weightage. The findings from the study could be useful in re-validating the UTM-TECS oral interaction scale so as to ensure its quality and to improve it tobecome a better yardstick for graduates’ employability and marketability.